2013
DOI: 10.1016/j.biochi.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of CblD interacts with CblC and influences intracellular cobalamin partitioning

Abstract: Mutations in cobalamin or B12 trafficking genes needed for cofactor assimilation and targeting lead to inborn errors of cobalamin metabolism. The gene corresponding to one of these loci, cblD, affects both the mitochondrial and cytoplasmic pathways for B12 processing. We have demonstrated that fibroblast cell lines from patients with mutations in CblD, can dealkylate exogenously supplied methylcobalamin (MeCbl), an activity catalyzed by the CblC protein, but show imbalanced intracellular partitioning of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 41 publications
(65 reference statements)
4
51
0
Order By: Relevance
“…When first identified, it was speculated, based on weak primary sequence homology, to be an ATPase and/or to bind cobalamin (11). However, subsequent biochemical studies revealed that human CblD alone is incapable of binding cobalamin or hydrolyzing ATP (22,23). So far, no ligand binding or enzymatic activity has been demonstrated for CblD.…”
mentioning
confidence: 99%
“…When first identified, it was speculated, based on weak primary sequence homology, to be an ATPase and/or to bind cobalamin (11). However, subsequent biochemical studies revealed that human CblD alone is incapable of binding cobalamin or hydrolyzing ATP (22,23). So far, no ligand binding or enzymatic activity has been demonstrated for CblD.…”
mentioning
confidence: 99%
“…It does not appear to bind cobalamin. The MMADHC protein is present both in the cytoplasm, where it binds the cobalamin chaperone protein MMACHC (mutated in the cblC inborn error) and in the mitochondria (Deme et al 2012;Gherasim et al 2013;Mah et al 2013). It is not understood how the protein directs cobalamin to different cellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The protein binder TC undergoes degradation in the lysosome, liberating vitamin B 12 that is subsequently exported out of this compartment using the transporters LMBR1 Domain Containing 1 (LMBRD1) 47,48 and ATP Binding Cassette Subfamily D Member 4 (ABCD4). 49,50 Once in the cytosol, newly internalized vitamin B 12 undergoes processing and trafficking by proteins, CblC [51][52][53][54][55][56][57] and CblD, [58][59][60][61][62][63] respectively, to finally reach acceptor proteins, MS in the cytosol and MCM in the mitochondrion.…”
Section: Vitamin B 12 Metabolismmentioning
confidence: 99%